2015
DOI: 10.1159/000381802
|View full text |Cite
|
Sign up to set email alerts
|

Development of Late-Onset Preeclampsia in Association with Road Densities as a Proxy for Traffic-Related Air Pollution

Abstract: Introduction: Previous epidemiological studies indicate an association between maternal exposure to air pollution and an increased risk of hypertensive disorders in pregnancy. We analyzed the association between the occurrence of mild/severe and early-/late-onset preeclampsia (PE) and traffic-related air pollution (TRAP). Materials and Methods: Based on retrospective data, 50 pregnant women with PE were selected and matched with a control group of healthy pregnant women according to their age, parity, and numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Briefly, the 28 investigations were published between 2006–2018 with sample sizes ranging from 58 to 1.21 million women. There were 6 studies on POP (Eslami et al 2016; Murray et al 2018; Savitz et al 2012; 2014; Stein et al 2009; Starling et al 2014), one study on water contaminants (Carwile et al 2014), 11 investigations on air pollutants (Dadvand et al 2014; Lee et al 2013; Madsen et al 2017; Mendola et al 2016; Nahidi et al 2014; Pedersen et al 2017; Savitz et al 2015; Wang et al 2018b; Wesselink et al 2017; Wu et al 2016; Yorifuji et al 2015), 6 examining metals (Elongi Moyene et al 2016; Maduray et al 2017; Sandoval-Carrillo et al 2016; Laine et al 2015; Wang et al 2018a; Vigeh et al 2006), and 4 investigations evaluating non-persistent organic pollutants (Cantonwine et al 2016; Leclerc et al 2014; Ye et al 2017; Shaw et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the 28 investigations were published between 2006–2018 with sample sizes ranging from 58 to 1.21 million women. There were 6 studies on POP (Eslami et al 2016; Murray et al 2018; Savitz et al 2012; 2014; Stein et al 2009; Starling et al 2014), one study on water contaminants (Carwile et al 2014), 11 investigations on air pollutants (Dadvand et al 2014; Lee et al 2013; Madsen et al 2017; Mendola et al 2016; Nahidi et al 2014; Pedersen et al 2017; Savitz et al 2015; Wang et al 2018b; Wesselink et al 2017; Wu et al 2016; Yorifuji et al 2015), 6 examining metals (Elongi Moyene et al 2016; Maduray et al 2017; Sandoval-Carrillo et al 2016; Laine et al 2015; Wang et al 2018a; Vigeh et al 2006), and 4 investigations evaluating non-persistent organic pollutants (Cantonwine et al 2016; Leclerc et al 2014; Ye et al 2017; Shaw et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies examined traffic exposure and three of these used proximity to major roadways as their exposure metric (Yorifuji et al 2015; Wesselink et al 2017; Wu et al 2016; Madsen et al 2017). These investigations considered the overall effect of traffic exposure rather than attempting to separate individual pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have found mixed results when using road proximity as a proxy for traffic-related air pollution, with some demonstrating an increased risk of SGA among those living closest to major roadways [ 19 , 20 , 21 , 22 , 23 ], while others show no association [ 17 , 24 ]. Likewise, findings for exposure to traffic and the risk of preeclampsia [ 15 , 16 , 17 , 25 , 26 , 27 ] are inconsistent. The use of SGA as a marker of intrauterine growth restriction, the complex etiology of preeclampsia, as well as varying definitions and categorizations of traffic exposure, may contribute to the inconsistency in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial literature assessing the association between the individual components (preeclampsia, placental abruption, and intrauterine growth restriction) of ischemic placental disease and air pollution exposures. Prior studies have found evidence of a positive association between traffic and the risk of preeclampsia [ 15 , 16 , 17 , 18 ] and intrauterine growth restriction, in addition to other adverse pregnancy outcomes [ 19 , 20 , 21 , 22 , 23 ]; however, some studies have found no association [ 17 , 24 , 25 , 26 , 27 ]. Studies exhibit substantial heterogeneity, particularly in exposure assessment methods.…”
Section: Introductionmentioning
confidence: 99%
“…These features vary between early and late onset forms, with placental deficiencies, such an inadequate modification of the spiral arteries and infarction, being more pronounced in cases with eoPE than in the late onset form ( 18 , 26 ). On the other hand, maternal inflammation appears to be a key contributor to the development of loPE, because it can be triggered by extraneous influences such as air pollution or obesity ( 15 , 26 , 30 ).…”
Section: Pe and Diabetes—a Complex Relationshipmentioning
confidence: 99%